Effectiveness of Ombitasvir with Paritaprevir/Ritonavir plus Ribavirin on the Treatment of Naïve Patients with Chronic Hepatitis C Virus Genotype 4 - Abdel-GAbbar, Mohammed; Alkot, Mohammed; Abdel-Moneim, Adel (Iraqi Journal of Pharmaceutical Sciences, 2022)
Background Direct-acting antivirals (DAAs) combination therapies from various mechanisms of action and families have been revolutionized the management landscape of chronic hepatitis C virus (HCV). Ombitasvir, paritaprevir with ritonavir (OBV/PTV/r) ± ribavirin (RBV) is approved to treat HCV genotype 4 (GT4) infection. Here, our objective was to delineate the efficacy and safety of OBV/PTV/r plus RBV in treating of Egyptian naïve patients infected with HCV GT4.Methods a cohort of 100 Egyptian patients infected with HCV GT4 was allocated and administered orally OBV/PTV/r with RBV. The primary endpoint of our study was a sustained virological response (HCV RNA < 12 IU/mL) 12 weeks after the cessation of the treatment (SVR12). This study is registered with ClinicalTrials.gov, number NCT04378608.Results Among treatment naïve patients with OBV/PTV/r+ RBV, SVR12 rates achieved 97% (97/100) in overall patients. Regarding treatment failure, the regimen recorded 3 % had treatment failure (0 null-responses, 3 relapses). However, the most frequently common adverse events recorded were a headache (28%), fatigue (18%), asthenia (23%), nausea (19%) and dyspnea (14%).Conclusions The interferon-free regimen combination of OBV/PTV/r plus RBV achieved excellent SVR12 rates, 97%, with virologic outcome failures 3%, and it was generally safe and well tolerated for treating naïve patients infected with HCV GT4.